Clinical characteristics, treatment patterns, and economic burden in patients treated for neuroendocrine tumors in the United States: a retrospective cohort study. (February 2015) - Chuang, Chien-Chia; Bhurke, Sharvari; Chen, Shin-Yin; Brulais, Siham; Gabriel, Sylvie
Abstract Objective: To assess patient characteristics, treatment patterns, and healthcare resource utilization (HRU)/costs of individuals treated for neuroendocrine tumors (NETs) in the US. Methods: Using a US administrative claims database, this study identified commercially-insured adults newly diagnosed with carcinoid tumors (ICD-9-CM: 209.xx) or pancreatic islet cell tumors (ICD-9-CM: 157.4 and 211.7) between July 1, 2007 and December 31, 2010 (date of first observed diagnosis denoted the index date). Patients were required to have 6-month pre-index and 12-month post-index continuous enrollment, and treatment by medical and/or surgical therapy during the 12-month follow-up. Descriptive analyses were performed to assess demographic/clinical characteristics, treatment patterns, HRU, and total healthcare cost in two mutually exclusive cohorts, medical and surgical therapy. Results: This study included 625 individuals with NETs treated with medical therapy (mean age: 54.2 years; 53.4% female) and 831 treated with surgical therapy (mean age: 51.3 years; 52.6% female). Among the medical therapy cohort, carcinoid syndrome (72.3%), liver metastasis (62.6%), and diarrhea (28.3%) were the most prevalent symptoms/co-morbidities in the 12-month post-index period; 92.3% received octreotide long-acting release, 35.8% had hospitalization admissions, and 37.9% had emergency room visits. The total monthly healthcare cost increased from $5629.7 in the pre-index period to $9093.3 in the post-index period. Among the surgical therapy cohort, carcinoid syndrome (40.3%), nausea and/or vomiting (28.5%), and liver metastasis (24.3%) were the most prevalent symptoms/comorbidities in the 12-month post-index period; 31.4% received surgical resection or removal of large intestine, 94.7% had hospitalization admissions, and 45.5% had emergency room visits. The total monthly healthcare cost increased from $2547.9 in the pre-index period to $8810.4 in the post-index period. Conclusion: Substantial clinical and economic burden exists among individuals with NET treated with medical or surgical therapies. Future research should investigate this treated sub-population considering a longer follow-up due to slow disease progression.